The Effect of Learning Motivation Towards Arabic Learning Outcomes at MA Al-Mahrusiyah Lirboyo Kediri - Mu'min Firmansyah; Anggia Rahmawati (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
This study aims to determine the effect of learning motivation on the learning outcomes of students in Arabic class X MA Al-Mahrusiyah Lirboyo Kediri. This research uses quantitative research. From the results of this study, it was found that based on the analysis of the learning motivation variable using SPSS Statistic 25.0, it was found that the most student motivation category data was in the Very High Arabic Learning Motivation category, namely 52 students (46%). Based on the Value and Category table, it can be seen that the highest number of students in the Arabic Language Learning Outcomes Value Category is 39 students with a percentage of 34.5%. From the results of the Pearson Correlation, it is found that the correlation between the Learning Motivation variable (X) on the Arabic Learning Outcomes (Y) is 0.927. According to the level of closeness, the relationship between the independent variable (Learning Motivation) and Arabic Learning Outcomes (Y) shows a high and strong relationship. While the direction of the relationship is positive. Based on these data it can be concluded that the higher the level of student motivation, the higher the results of learning Arabic for class X MA Al-Mahrusiyah Lirboyo Kediri. From the test results using the Kolmogorov-Smirnov test, it shows that the value of P. value = 0.103 or greater than Î± = 0.05, so it can be concluded that the residual is normally distributed. And the magnitude of the correlation value (R) is 0.959. From this output, a determinant coefficient (R Square) of 0.859 contains the understanding that the influence of the independent variable Learning Motivation (X) on the dependent variable Arabic Learning Outcomes (Y) is 85.9%.